Identification and Analysis of Entrepreneurial Strategies preserving Schumpeterian Rent - Asadi Sisakht, Keyhan; Jalili Orumieh, Sharareh; Talebi, Kambeiz (Journal of Entrepreneurship, Business and Economics; Vol 2 No 1 (2014), 2014)
Purpose- As any increase in the price of resources and any imitation by competitors decrease entre-preneurial rent, the entrepreneurs should use some kind of strategies to preserve this rent. We used resource based view as a lens for finding these strategies. Design/methodology/approach- For conducting this research, qualitative method was used and qual-itative research questionnaire was formed based on Peteraf model, 15 entrepreneurial companies have participated for completing this study. Findings A total of 13 strategies have been identified and analyzed which are: Pioneering strategy, Economy of Scale, Establishing reputation and brand, Creating continuous innovation, Secrecy and ambiguity strategy, Franchise development, Control of resources, Legal barriers, Compromise with competitors, Selecting strategic location for business, Sharing profit with resource owners, Supplier diversification and Vertical integration. Research Implications- Entrepreneurs can use these strategies to preserve their rent. In addition, the researchers can use these results for further research and developing the literature of entrepreneurial strategies which was not rich before presenting this research. Originality/value- This is the first qualitative research which tries to identify entrepreneurial strate-gies through the resource-based view lens. Furthermore the research tries to differentiate entrepre-neurial strategies from non-entrepreneurial strategies for the first time. Conceptual Paper Reference to this paper should be made as follows: Asadi Sisakht, K., Jalili Orumieh, S., Talebi, K. (2014). “Identification and Analysis of Entrepreneurial Strategies preserving Schumpeterian Rent”, Journal of Entrepreneurship, Business and Economics, Vol. 2, No. 1, pp. 41–62.